1990
DOI: 10.1111/j.2044-8295.1990.tb02347.x
|View full text |Cite
|
Sign up to set email alerts
|

Social remembering: Quantitative aspects individual and collaborative remembering police officers and students

Abstract: Psychologists have generally investigated remembering as an intrapersonal phenomenon. However, everyday remembering often has a more social interpersonal flavour, particularly when two (or more) people jointly recall and discuss an event they have experienced or witnessed. This study examines quantitative differences between individual, dyadic and four-person group free and cued recall of a purposive social interaction -a fictional police interrogation -and contrasts the findings from two subject samples, poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
37
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 22 publications
6
37
2
Order By: Relevance
“…That position was initially advocated by Shaw (1932) for problem solving tasks. The majority of investigators studying accuracy of memory in groups (Hartwick, Sheppard, & Davis, 1982;Clark, Stephenson, & Kniveton, 1990;Hinsz, 1990;Stephenson, Clark, & Wade, 1986;Vollrath, Sheppard, Hinsz, & Davis, 1989;Warnick & Sanders, 1980) agreed with Shaw's position. However, even within studies advocating error rejection in groups, exceptions can be found.…”
mentioning
confidence: 55%
“…That position was initially advocated by Shaw (1932) for problem solving tasks. The majority of investigators studying accuracy of memory in groups (Hartwick, Sheppard, & Davis, 1982;Clark, Stephenson, & Kniveton, 1990;Hinsz, 1990;Stephenson, Clark, & Wade, 1986;Vollrath, Sheppard, Hinsz, & Davis, 1989;Warnick & Sanders, 1980) agreed with Shaw's position. However, even within studies advocating error rejection in groups, exceptions can be found.…”
mentioning
confidence: 55%
“…The finding that real groups recall less than nominal groups is highly robust (e.g., Basden, Basden, Bryner, & Thomas, 1997;N. Clark, Stephenson, & Kniveton, 1990;Finlay, Hitch, & Meudell, 2000;Hartwick, Sheppard, & Davis, 1982;Morrissett, Crannell, & Switzer, 1964;Stephenson, N. Clark, & Wade, 1986;Weldon & Bellinger, 1997;Weldon, Blair, & Huebsch, 2000;Wright & Klumpp, 2004).…”
mentioning
confidence: 95%
“…For example, it is commonly believed that "two heads are better than one," and research indicates that when people collaborate to recall an event the group does remember more than individuals working alone (e.g., Clark, Stephenson, & Kniveton, 1990;Dashiell, 1935;Hoppe, 1962;Lorge & Solomon, 1961;Stephenson, Brandstatter, & Wagner, 1983;Yuker, 1955). However, the question arises as to whether group recall is better than, equal to, or worse than the sum of the individual recalls.…”
Section: Collaborative and Individual Recallmentioning
confidence: 99%